2023
DOI: 10.1002/smll.202207266
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Metal‐Thiocatecholate Functionalized UiO‐66 Framework for Photocatalytic Hydrogen Evolution Reaction

Abstract: Exploiting clean energy is essential for sustainable development and sunlight‐driven photocatalytic water splitting represents one of the most promising approaches toward this goal. Metal‐organic frameworks (MOFs) are competent photocatalysts owing to their tailorable functionality, well‐defined structure, and high porosity. Yet, the introduction of the unambiguous metal‐centered active site into MOFs is still challenging since framework motifs capable of anchoring metal ions firmly are lacking. Herein, the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 56 publications
0
9
1
Order By: Relevance
“…The surface area of Ce-aMOFs was derived to be ca. 6.69 m 2 g −1 , which was significantly smaller than that reported in the references for normal MOFs 40,41 (Fig. 1C), due to the non-porous feature of aMOFs.…”
Section: Resultscontrasting
confidence: 60%
“…The surface area of Ce-aMOFs was derived to be ca. 6.69 m 2 g −1 , which was significantly smaller than that reported in the references for normal MOFs 40,41 (Fig. 1C), due to the non-porous feature of aMOFs.…”
Section: Resultscontrasting
confidence: 60%
“…43,44 The easy post-synthesis surface functionalization of organic moieties provided a great chance to design organic-inorganic hybrids with a high porosity used in various energy applications. 45,46 On the other hand, it is possible to transform MOFs into their derivatives, which possess signicant electro-catalytic activities, mainly found in bimetallic MOFs. 47 The optimal structural stability of MOFs for various energy applications can be achieved by modifying their pathways as single MOFs, composites, and derivatives (Fig.…”
Section: Deepak P: Dubalmentioning
confidence: 99%
“…Metalloporphyrin (MTFPP) guest also acts as a robust anchor of the photocatalyst, preventing the catalyst's leaching and increasing recyclability. UiO-66-DCBDT-M (M = Fe, Ni, Cu) synthesized by Zhong et al 112 were examined for the photocatalytic H 2 evolution reaction, where UiO-66-DCBDT-Cu shows the best result. The noble metal free heterojunction UiO-66-DCBDT-Cu@TiO 2 shows the HER rate of 12.63 mmol g −1 h −1 (Table 16, entry no.…”
Section: Applicationsmentioning
confidence: 99%
“…6) synthesized from thiol-based ligand L 3 with UiO-66 topology. 112 The presence of the thiol group in the 2,3 position of the ligand allows the incorporation of a transition metal by chelation (M = Fe, Ni or Cu) to synthesize UiO-66-DCBDT-M photocatalyst. Gui et al reported ZrDMTD (Fig.…”
Section: Perspectivementioning
confidence: 99%